STRATEGY OF FREIGHT FORWARDER COMPANIES IN RESOLVING IMPORT DELAY - Bunga Tiur Annisa Rulyanni; Mashudi Mashudi (Antis Publisher, 2026)
Objective: This research is based on recurring problems in the import process delays, particularly those caused by national holidays. Such delays often lead to congestion in the days following the holidays, resulting in container backlogs that must be cleared immediately. Additional contributing factors include limited availability of trucking vendor fleets, hindered communication with related parties, and overloaded service systems. The objective of this study is to identify strategies for resolving import delays and to evaluate the supporting and inhibiting factors within the process. Method: The research method employed is descriptive qualitative, with data collected through interviews, observations, and documentation. Results: The results of the study indicate that the strategies implemented by the company include the optimization of documentation processes, coordination with relevant agencies, and the use of information technology for cargo tracking. The key supporting factor is the availability of competent human resources, while the main obstacles stem from regulatory changes and delays caused by third parties such as customs or logistics partners. Novelty: These findings are expected to contribute to the development of logistics management in the import sector.